Analysis of the Effect of Problem-Based Learning on Leadership Skills - Hasan, Hanapi; Giatman, M; Maksum, Hasan (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2024)
Educators have developed a model to facilitate the learning of various competencies and the assessment of student understanding. The methods applied include lectures, assignments to be completed at home, and written exams. Meanwhile, to develop non-technical competencies such as leadership skills, a more comprehensive approach is required. This article outlines the findings of a controlled study that implemented Problem-Based Learning (PBL) to teach these skills. The effectiveness of this method was measured using the Competing Value Framework (CVF) developed by Quinn in 2004. The research results indicate a significant statistical improvement in students' ability to set goals and identify and organize activities to achieve these goals. The included literature review also emphasizes the suitability of PBL in teaching both technical and non-technical competencies.